(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The banking sector of all kinds is the backbone of the economy in all countries, as it is the main financier of most economic projects in order to achieve economic development and achieve stability, which contributes to providing the necessary resources in return for obtaining a profit margin in exchange for giving up his money and bearing credit risks. Among the aforementioned banking sectors are: Islamic banks that invest their capital in several forms in order to obtain profits that enable them to continue and grow, and the most important of these formulas is the Murabaha formula, which is summarized by the bank selling a commodity after owning it and then selling it to the applicant for this commodity based on a prior request and the bank’s promise to buy it in exchange for the bank’s receipt On a specific percentage of the profits, if there is a contract between the Islamic bank (the seller) and the customer (the buyer) documenting the details of the contract, provided that the buyer pays the amount of the sale with the profits in the form of monthly installments or according to what is agreed upon.